TEACHERS' EXPERIENCE IN DIGITAL-BASED ISLAMIC RELIGIOUS EDUCATION LEARNING MANAGEMENT INNOVATION: A PHENOMENOLOGICAL STUDY - Jufri; Andi Fadhilah A. Natsir (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
Digital transformation in education has driven significant changes in learning management practices, including in Islamic Religious Education (PAI). Teachers no longer only play the role of material presenters, but also digital learning managers who must be able to design, manage, and evaluate technology-based learning processes. This research aims to understand the lived experience of teachers in innovating digital-based PAI learning management. The research uses a qualitative approach with phenomenological methods. The research participants consisted of PAI teachers who actively use digital platforms in learning. Data were collected through in-depth interviews, digital learning observations, and documentation, then analyzed using thematic phenomenological analysis techniques. The results of the study show that digital learning management innovations are carried out through: (1) digital platform-based learning planning, (2) virtual management of religious interactions, (3) technology-based evaluation strategies, and (4) pedagogical adaptation to the characteristics of the digital generation. The main challenges include teachers' digital literacy, limited infrastructure, and internalization of spiritual values in the digital space. This research emphasizes that digital innovation in PAI is not just the use of technology, but the transformation of pedagogic paradigms and religious learning management. These findings contribute to the development of a contextual and humanistic, digital-based PAI learning management model